Examining the impact of management innovation strategies on achieving competitive advantage from the point of view of the senior and executive departments of Ba Jaafar Medical Group - Sudan - Osman, Muzmal Ali Mohamed (Journal of Economic, Administrative and Legal Sciences, 2017)
This study aimed at testing the effect of the strategies of the administrative creativity, on achieving competition, as viewed by the high and middle administrators of Bajafar medical group in the Sudan. This is to point out the significance of being responsible for the strategies of administration and its elements (smart joint ventures - strategies of aim-based administration – strategies of specialization - strategies of groups of work) and the effect of this in creating competition among works, and it has been distributed (50) questionnaires and it was retrieved (45) questionnaires. The descriptive analytical method was used. A questionnaire was designed for data collection. Many statistical methods were used; Cronbach’s alpha factor analysis , person correlation ; analysis of falling the study result in the fact that there is a significant statistical relation between the strategies of creative administration and the achievement of competition – the study recommended : the application of the findings of the study on similar institution . Establishing a unit to foster creativity and creators with real cash incentive. This will ensure complete dependence on the strategies of creativity in creating compotation to be culture of work. Connecting the system of work with thrilling and provoking way to complete actively. Drawing creators through building relation with the universities and instituted. Not to be hesitant to apply any new trends irrespective of their consequences .